Ablation of typical atrial flutter using mini electrode measurements for maximum voltage‐guided ablation: A randomized, controlled trial. Issue 1 (9th December 2021) - Rowe, Matthew K.; Claughton, Andrew; Davis, Jason; Yee, Lauren; Kaye, Gerald C.; Dauber, Kieran; Hill, John; Gould, Paul A.
Abstract: Background: Novel ablation catheters with mini electrode (ME) sensing have become available but their utility is unclear. We investigated whether ablation of the cavotricuspid isthmus (CTI) for atrial flutter (AFL) would be improved using ME signals. Methods: Sixty‐one patients (76% male, 63 ± 10 years) with CTI‐dependent AFL underwent ablation using a maximum voltage‐guided approach, randomized to either standard 8 mm non‐irrigated catheter with bipolar signals or IntellaTip MiFi catheter using ME signals alone. Results: Acute bidirectional block was achieved in 97%. Mean follow‐up was 16.7 ± 10 months. The median number of ablation lesions was 13 in both groups (range 3–62 vs. 1–43, p = .85). No significant differences were observed in AFL recurrences (17% vs. 11%, p = .7), median procedure durations (97 min [interquartile range (IQR), 71–121] vs. 87 min [IQR, 72–107], p = .55) or fluoroscopy times (31 min [IQR, 21–52] vs. 38 min [IQR, 25–70], p = .56). Amplitudes of ME signals were on average 160% greater than blinded bipolar signals. In 23.7% of lesions where bipolar signals were difficult to interpret, 13.6% showed a clear ME signal. Conclusions: There was no difference in the effectiveness of CTI ablation guided by ME signals, compared with using bipolar signals from a standard 8 mm ablation catheter. While ME signal amplitudes were larger and sometimes present when the bipolar signal was unclear, this did not improve procedural characteristics or outcomes. The results suggest future research should focus on lesion integrity rather than signal sensing. Abstract : In a randomized controlled trial during catheter ablation of typical atrial flutter, the use of mini electrode (ME) signals on the MiFi catheter was compared to standard of care bipolar signals on an 8‐mm catheter. While ME signal amplitudes were larger and sometimes present when bipolar signal was unclear, there was no difference in procedural characteristics or outcomes between the two groups.